Fuzzy position control / Suhaire Mustaita - Mustaita, Suhaire (1999)
The purpose of this project is to implement a control system using fuzzy logic controller which controls the position of the output shaft in the DC servomotor.The controller was designed based on the FuzzyTECH software. By applying fuzzy algorithms for single input and single output (SISO) problem in a DC servomotor, this project will investigates the possibility of faster and more accurate response compared with Proportional plus Derivative (PD) controller.